DISAIN PROSES KEAMANAN PANGAN PADA SISTEM MANAJEMEN INDUSTRI PAKAN UNGGAS - Legis Tsaniyah, Hartrisari Hardjomidjojo, dan Sapta Raharja (Jurnal Teknologi Industri Pertanian, 2017)
The feed industry shall maintain quality and food safety of their products. The research conducted in the year of 2015-2016 was to design the optimum condition of food safety consideration for feed industries in Indonesia.  Feed for livestock was formulated by using corn meal, soya protein, fish meals, rice bran, veterinary drugs, steam, and other ingredients. Growth promotor materials were formulated from vitamin, antibiotics, amino acid, methylene blue, and other trace elements also were added in the formulation. The feed ingredients are potential sources of food safety hazard in feed products. Result of model analysis found the major sources of food safety risks, i.e.1) veterinary drugs residues (X1); 2) aflatoxin potential in humid corn meals (X2), and3) alfatoxin potential in humid soya meal (X3). Minimisation model formulated for food safety in feed production was Z = 13.78 X1 + 10.00 X2 + 7.67 X3. The optimisation model by using simplex solution found maximum bioaccumulation value index of 93.33 per ton feed production. The verification model done for two feed industries and calculated bioaccumulation index were 20.16 and 24.43 per ton livestock feed production. The result concluded that the feed produced by both industries have been recommended safe to consume. The optimum condition for food safety in livestock feed industry interpreted from this optimal conditions.Keywords:  bioaccumulation index, food safety risk minimization, livestock feed industry